Correlação entre a posse de bola e passes corretos no Futebol : maior posse determina maior qualidade do passe de bola? - Silva, Sanderson Soares da (Educación Física y Ciencia.)
This study has compared ball possession and correct pass, in the Soccer first league from Spanish Championship (2016/2017), Argentine Championship (2016) and Brazilian Championship (2016). Moreover, we evaluated a possible correlation between the same variables, with the same groups. The sample was composed by tree teams classified at the annual ranking of the International Federation of Football History and Statistics - IFFHS/2015. Data analyses were presented by descriptive statistics and ANOVA, with Dunn's Post Hoc, between groups. Also, Pearson´s Correlation between ball possession and correct pass was done for each group. Our results did not show significant differences between the groups for ball possession. However, we found significant differences for correct pass between Spanish Championship versus Argentine Championship and between Argentine Championship versus Brazilian Championship. Also, we found a perfect correlation between ball possession and correct pass in the Argentine Championship, a good correlation in the Spanish Championship and a reasonable correlation in the Brazilian Championship. To conclude we agree on the fact that more studies are necessary, in order to make other comparisons, and apply other variables to determine better markers of success in high performance soccer teams.